Three-Dimensional Study of F. graminearum Colonisation of Stored Wheat: Post-Harvest Growth Patterns, Dry Matter Losses and Mycotoxin Contamination - Portell, Xavier; Verheecke-Vaessen, Carol; torrelles-Rafales, Rosa; Medina, Angel; Otten, Wilfred; Magan, Naresh; Garcia-Cela, Esther (Microorganisms, 2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/). Fusarium causes significant post-harvest quality losses and mycotoxin contamination instored wheat but the colonisation dynamics of the grain and how this may be affected by the initialinoculum position in the grain mass is poorly understood. This study examined the 3D growthkinetics and mycotoxin production (deoxynivalenol and zearalenone) by F. graminearum duringhyphal colonisation from different initial inoculum positions in wheat microcosms (top-centre,bottom-centre, and bottom-side) maintained at two water activities (aw; 0.95 and 0.97). Clear jarswere used to visually follow the colonisation dynamics. Fungal respiration and associated drymatter loss (DML) and ergosterol were also quantified. Colonisation dynamics was shown to beaffected by the inoculation position. At the end of the colonisation process, fungal respiration andDML were driven by the inoculation position, and the latter also by the prevailing aw. Fungalbiomass (ergosterol) was mainly affected by the aw. The initial inoculum position did not affect therelative mycotoxin production. There was a positive correlation between respiration and ergosterol,and between mycotoxin production and colonisation indicators. We suggest that spatially explicitpredictive models can be used to better understand the colonisation patterns and mycotoxincontamination of stored cereal commodities and to aid more effective post-harvest management. Peer reviewed